Correlation of the severity of the clinical presentation of SARS-CoV-2 pneumonia with respiratory function parameters in the post-COVID period - Belic, Slobodan; Ivanovic, Andjelka; Todorovic, Aleksandra; Maric, Nikola; Milic, Sandra; Perić, Jovan; Stjepanović, Mihailo; Krajisnik, Snjezana; Milosevic, Ivana; Jankovic, Jelena (The Journal of Infection in Developing Countries, 2024)
Introduction: Since COVID-19 first surfaced in 2019, it has seriously threatened public health. The most prevalent symptoms are respiratory ones. This study aimed to present the correlation between the severity of the clinical presentation of the disease and the results of respiratory function tests conducted within 6 months after hospital discharge. Methodology: This retrospective study included 99 patients with confirmed SARS-CoV-2 virus infection. Of all patients 24.2% had accentuated bronchovascular pattern, 9.1% had unilateral, and 29.3% had bilateral pneumonia. In comparison, 35.4% patients had diffuse changes, which were described as acute respiratory distress syndrome (ARDS) on computed tomography (CT). Results: Patients with unilateral, bilateral pneumonia or diffuse lung damage had significantly lower forced vital capacity (FVC) values. They were treated with non-invasive mechanical ventilation (NIV) or invasive mechanical ventilation (MV) and had lower FVC values (0.039). A negative, weak correlation existed between CT findings during the infection and Diffusing capacity for carbon monoxide (DLCO) measured after the infection (0.003). A negative, weak correlation was found between oxygen therapy, the use of NIV, and MV findings during the infection with DLCO. A negative correlation was noted between leukocyte values during the infection and forced expiratory volume in the first second (FEV1) and FVC after the infection. Conclusions: Patients with COVID-19 infection who need oxygen support and MV continue to suffer from loss of respiratory function after the resolution of COVID-19 infection. These findings highlight the negative predictive value of pulmonary tests in the long-term follow-up for the development of PC-ILD as well as decreased pulmonary capacity.